2012
DOI: 10.1007/s10995-012-1079-7
|View full text |Cite
|
Sign up to set email alerts
|

Labor Management and Mode of Delivery Among Migrant and Spanish Women: Does the Variability Reflect Differences in Obstetric Decisions According to Ethnic Origin?

Abstract: Based on previous findings showing both better birth outcomes in migrant than in Spanish women and different rates of medical intervention according to mother's origin, we hypothesize that mode of delivery decisions to solve similar problems differ according to ethnic origin. Ethnic differences for maternal characteristics, medical intervention, and mode of delivery were evaluated in 16,589 births from a Maternity Hospital in Madrid (Spain). Multinomial logistic regression analysis was used to evaluate the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…This study has largely confirmed previous results, based both on population data and vital records [13,[20][21][22], which showed significant differences in reproductive patterns and perinatal characteristics between Spanish and immigrant mothers. Our findings also show that ethnic differences in reproductive patterns remain constant (or even increase) throughout the analyzed period, whereas the ethnic characteristics in mode of delivery and perinatal health converge with the predominant pattern of the Spanish mothers, despite still showing some quantitative differences.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This study has largely confirmed previous results, based both on population data and vital records [13,[20][21][22], which showed significant differences in reproductive patterns and perinatal characteristics between Spanish and immigrant mothers. Our findings also show that ethnic differences in reproductive patterns remain constant (or even increase) throughout the analyzed period, whereas the ethnic characteristics in mode of delivery and perinatal health converge with the predominant pattern of the Spanish mothers, despite still showing some quantitative differences.…”
Section: Discussionsupporting
confidence: 91%
“…Spanish mothers were older, more often primiparous, and have higher rates of multiple births compared with immigrants mothers. Finally, recent results [21,22] reinforce the idea that increasing obstetric interventions might be contributing to the increasing trend of low birth weight and late preterm deliveries in Spain, where Caesarean section rates and other medical interventions during birth are in the highest range among European countries [7].…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…A total of 27 studies addressed maternal and child health [ 144 - 170 ] (Additional file 12 ). The use of caesarean section (CS) was consistently higher in HAs vs locals [ 146 , 149 - 153 , 160 , 166 ] and all the studies that investigated rates of low birth weight (LBW) except for two [ 151 , 165 ] found that these were higher [ 144 , 158 - 161 , 166 ] or similar [ 153 ] in children born to local women. However, in Finland, newborns to Latin-American mothers had more interventions after birth and higher perinatal mortality [ 151 ] and in Sweden, the risk of non-normal birth was 50% higher [ 163 ].…”
Section: Resultsmentioning
confidence: 99%
“…In Spain, as in other Western populations, the change in the environmental conditions affecting pregnancy and birth outcome has been remarkable from the beginning of the 20 th Century, affecting the maternal system determinants (Bernis 2009;Varea, 2009;Varea et al 2012), the socio-sanitary system Bernis et al 2013;Varea et al 2012) and different aspects of neonatal biology, which are jointly examined in this study (sex ratio, mortality rate, weight, gestational age and sex differences). Sex differences show that males present higher birth weight, lower gestational age and a greater contribution to live births and early infant deaths.…”
Section: Discussionmentioning
confidence: 99%